Microsoft Corp. : branding and positioning .NET - Sawhney, Mohanbir; Buenneke, Brian; Jackson, Lisa; Kulick, Lisa; Kulick, Nancy; Norton, Evan; Post, Erica; Rotem, Ran (London : SAGE Publications Ltd, 2017)
John Williams, senior director of marketing for Microsoft's .NET, was trying to build the .NET brand, a comprehensive family of next-generation connectivity software products. Highlights the challenges of branding and positioning a complex technology offering. The first challenge facing Microsoft was to develop a common definition of .NET, which had been in flux over the prior two years. The second challenge was to choose between an umbrella branding strategy, a sub-branding strategy, and an ingredient branding strategy. The third challenge was to create a value proposition that would appeal to three very different target audiences: business decision makers, IT professionals, and developers.
Originally published: Sawhney, M., Buenneke, B., Jackson, L., Kulick, L., & Kulick, N., Norton, E., Post, E., & Rotem, R. (2002). Microsoft Corp.: Branding and Positioning .NET. 5-104-034. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; William, John; Microsoft Corporation; Microsoft .NET -- Case studies; Microsoft .NET Framework -- Case studies; Application software -- Case studies; Branding (Marketing) -- Case studies